Development and validation of a resource material on principles of speech therapy for individuals with cleft lip and palate: A short video film in Tamil - Reethee M Antony; Roopa Nagarajan; Savitha Vadakkanthara Hariharan; Subramaniyan Balasubramaniyan (Wolters Kluwer Medknow Publications, 2016)
Background: Community-based rehabilitation (CBR) by trained and supervised CBR workers is an emerging alternate mode of service delivery for providing speech correction. Resource material in the vernacular language is essential to aid CBR workers. There is no step-by-step training material that could be used in Tamil language. Aims: To develop and validate a video film in Tamil for CBR workers/parents/caregivers on basic principles of speech therapy for individuals with cleft palate. Materials and Methods: The method involved the development of a short video film and evaluation of its validity. The development phase included designing the content, developing the script of the film, selecting participants, and shooting of the video film. The validation of the video film involved developing a video evaluation form, screening the video film, and administrating the video evaluation form. Thirty participants including 20 speech-language pathologists, five CBR workers, and five technical experts in filmmaking were involved in the process of validation. Statistical Analysis: Cronbach's alpha was used to estimate content validity; descriptive statistics to analyze results of the video evaluation form. Results: Cronbach's alpha was 0.863 indicative of a high content validity. The overall mean rating on the video evaluation form was 8.5 (standard deviation = 0.57). Conclusions: The results illustrate that the content and delivery style of the video film was appropriate. Further research is required to examine the efficacy of the video as a resource material in the training of CBR workers.